PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KEGUNAAN DAN PROMOSI PENJUALAN TERHADAP PEMBELIAN IMPULSIF - A. Q. Candra Mustika Intan H. P.; Herman Herman; Febrina Hambalah (Universitas Sahid, 2023)
The evolution of E-commerce into Social commerce is a new phenomenon in the development of trade in Indonesia. TikTok is one of the social media applications that has participated in this evolution until impulse buying behavior appears among TikTokShop users. Several factors that influence impulse buying in social commerce, especially TikTokShop, are website and marketing factors. Based on this, this study was conducted to explain how the effect of kemudahan yang dirasakan, perceived usefulness, and sales promotion on impulse buying of fashion products by TikTokShop users in Surabaya. This research was conducted using quantitative methods with the type of explanatory research. This research was conducted in Surabaya with the criteria of respondents being TikTokShop users in Surabaya who had shopped at TikTokShop and had bought fashion products at TikTokShop impulsively. The sampling technique was carried out using non-probabilty sampling and purposive sampling with a research sample of 96 respondents, and data analysis using multiple linear regression analysis with the help of the SPSS (Statistical Program for Social Science) version 25.0 program. The results of this study can be said that the perceived ease of use, perceived usefulness, and sales promotions have a significant positive effect partially and simultaneously on the impulse buying of fashion products by TikTokShop users in Surabaya.